Feasibility of extracorporeal membrane oxygenation cardiopulmonary resuscitation by low volume centers in Belgium - Paul B. Massion; Sabrina Joachim; Philippe Morimont; Guy‐Loup Dulière; Romain Betz; Arnaud Benoit; Philippe Amabili; Marc Lagny; Justin Lizin; Anthony Massaro; Vincent Tchana‐Sato; Didier Ledoux (Journal of the American College of Emergency Physicians Open)
Abstract Objective To assess the feasibility of delivering extracorporeal cardiopulmonary resuscitation (ECPR) in refractory out‐of‐hospital cardiac arrests (OHCA) by low volume extracorporeal membrane oxygenation (ECMO) centers and to explore pre‐ECPR predictors of survival. Methods Between 2016 and 2020, we studied 21 ECPR patients admitted in 2 tertiary ECMO centers in Liège, Belgium. Our ECPR protocol was based on 6 prehospital criteria (no flow < 3 minutes, low flow < 60 minutes, initial shockable rhythm, end‐tidal CO2 > 15 mmHg, age < 65 years, and absence of comorbidities). A dedicated training, prehospital checklist and call number for 24/7 ECMO team assistance were implemented. Hemodynamics and blood gases on admission also were assessed. Results Twenty‐one (28%) out of 75 refractory OHCA patients referred were treated by ECPR, with a hospital survival rate of 43% (n = 9/21), comparable to ECPR results from the international extracorporeal life support organization registry. Transient return of spontaneous circulation before ECPR (89% in survivors vs 17% in non‐survivors, P = 0.002) and higher initial serum bicarbonate (med [P25‐P75] 14.0 [10.6–15.2] vs 7.5 [3.7–10.5] mmol/L, P = 0.019) or lower initial base deficit (14.9 [11.9–18.2] vs 21.6 [17.9–28.9] mmol/L, P = 0.039) were associated with a more favorable outcome. Conclusion In low volume ECMO centers, the implementation of a specific ECPR protocol for refractory OHCA patients is feasible and provides potential clinical benefit. Highly selective inclusion criteria seem essential to select candidates for ECPR. Initial serum bicarbonate and base deficit integrating cumulative cell failure may be relevant pre‐ECMO prognostic factors and require larger‐scale evaluation.